Pension Reform, Ownership Structure, and Corporate Governance: Evidence from a Natural Experiment - Giannetti, Mariassunta; Laeven, Luc (Review of Financial Studies, 2009)
[Sweden offers a unique natural experiment to analyze the effects of institutionalized saving on the ownership structure, corporate governance, and firm performance. The Swedish pension reform increased the stock market participation of pension funds, causing a significant reshuffling in the ownership of pension funds. We show that the effects of institutional investment on firm performance depend on the industry structure of pension funds. Firm valuation improves if public pension funds and large independent private pension funds increase their shareholdings. Additionally, controlling shareholders appear reluctant to relinquish control and the control premium increases if public pension funds acquire shares.]